Simple Colorimetric Method Using Aqueous Solution to Detect Heavy Metal - Abed, Thakir H.; Kadem, Burak Y.; . Kadhim, Raheem G (Iraqi Journal of Science, 2019)
Simple method has been used to determine the absence of heavy metals in an aqueous solution. Fluorescein was used as the base colorimetric materialThis was doped with CuCl2 and the final solution showeda clear change in color. This change was correlated with the change in both pH and electrical conductivity of the solution. The optical property as an obvious change of the spectra was observed. Therefore, this simple method could be proposed as a method to detectheavy metals in any solution.